2018
DOI: 10.14710/teknik.v38i2.12942
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Jenis dan Karakteristik Lempung di Perbukitan Jiwo, Bayat, Klaten dan Arahannya sebagai Bahan Galian Industri

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Soft soils include clay and silt types. In clay, soil characteristics can be observed directly in the field, which will crack when dry (shrink) and expand in wet conditions [7]. The grain size of silt soil is more significant than clay soil.…”
Section: Theoretical Of Soft Soilsmentioning
confidence: 99%
“…Soft soils include clay and silt types. In clay, soil characteristics can be observed directly in the field, which will crack when dry (shrink) and expand in wet conditions [7]. The grain size of silt soil is more significant than clay soil.…”
Section: Theoretical Of Soft Soilsmentioning
confidence: 99%
“…There are stranded metamorphic rocks in the form of schist and phyllite. These metamorphic rocks have undergone intensive weathering, which is characterized by the presence of red solid soil which subsequently produces clay [2].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Vichi et al shown that ceramic membrane material is suitable to be used as a membrane in MFC, since it has the main ingredients in the form of silica (SiO 2 ), Titania (TiO 3 ), and Alumina (Al 2 O 3 ) [5]. While, research carried out by Winarno et al indicated that the clay contains SiO 2 , TiO 3 , Fe 2 O 3 , TiO 2 [6]. Therefore, clay is expected to be a suitable material to be used as Proton Exchange Membrane (PEM).…”
Section: Introductionmentioning
confidence: 99%